2019
DOI: 10.2147/cmar.s219872
|View full text |Cite
|
Sign up to set email alerts
|

<p>Digital Immune-Related Gene Expression Signatures In High-Grade Serous Ovarian Carcinoma: Developing Prediction Models For Platinum Response</p>

Abstract: PurposeResponse to platinum-based therapy is a major prognostic factor in high-grade serous ovarian cancer (HGSOC). While the exact mechanisms of platinum-resistance remain unclear, evidence is accumulating for a connection between the organism’s immune-response and response to platinum. However, predictive tools are missing. This study was performed to examine the putative role of the genetic tumor immune-microenvironment in mediating differential chemotherapy response in HGSOC patients.Patients and methodsEx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…In addition, multiple reversions of germline BRCA1 or BRCA2 mutations, loss of BRCA1 promoter methylation, an alteration in molecular subtype, and overexpression of MDR1 were additional reasons of drug resistance. It was reported that a scoring system for platinum response in high-grade serous ovarian carcinoma was established ( 28 ). Gene expression signatures from TCGA-dataset were collected to identify 11 significantly differentially expressed genes associated with platinum response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple reversions of germline BRCA1 or BRCA2 mutations, loss of BRCA1 promoter methylation, an alteration in molecular subtype, and overexpression of MDR1 were additional reasons of drug resistance. It was reported that a scoring system for platinum response in high-grade serous ovarian carcinoma was established ( 28 ). Gene expression signatures from TCGA-dataset were collected to identify 11 significantly differentially expressed genes associated with platinum response.…”
Section: Discussionmentioning
confidence: 99%
“…Acquirement of resistance towards chemotherapeutics is a dynamic and multifactorial process influenced by cancer stem cell (CSC) enrichment (34). Several mechanisms leading to platinum resistance have been identified: reduced intracellular cisplatin accumulation due to alterations in transmembrane transport, activation of cell growth-promoting and DNA damage repair pathways, aberrant DNA methylation, enhanced epithelialto-mesenchymal transition, and reduced endocytosis of cisplatin (35)(36)(37). However, as there are no established tools for predicting response to platinum therapy, there is an unmet need for predictive factors helping to identify patients at high risk for platinum resistance to select the adequate treatment for individual patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the following methods were applied as it was described in ( 36 ). However, in this study the gene panel is custom-designed in order to fit genes associated with DSR.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, all target counts get multiplied by this normalization factor and afterwards mathematically rounded to integers. In addition to background subtraction, background noise was excluded by utilization of one-side Wilks t -test of negative controls and target specific counts in all samples to identify genes not relevantly expressed (p < 0.05) ( 36 ).…”
Section: Methodsmentioning
confidence: 99%